the relationship of self-disclosure with stress level on final level students in doing thesis at stikes santa elisabeth medan in 2021 - Lilis Novitarum; Imelda Derang; Gracia Fransiska Hasibuan (Jurnal EduHealth, 2022)
Self-disclosure is a person's ability to express problems and personal experiences to get a positive response so that a person is able to reduce stress levels. The results of the initial survey showed that 48.9% of students experienced severe stress and 51.1% experienced mild stress. This study aims to determine the relationship between self-disclosure and stress levels in final year students in doing thesis at STIKes Santa Elisabeth Medan in 2021. This study uses correlation research with a cross sectional design. The research population is 169 people with a total sample of 61, where the sample is taken by proportional sampling technique. Collecting respondent data was taken through a questionnaire using the google form application. Based on the results of the frequency distribution of stress levels in final year students, 15 people (24.6%) were obtained in the high category and 46 people in the low category (75.4%). In self-disclosure, there were 44 people (72.1%) in the high category and 17 people (27.9%) in the low category. The results of the chi square statistical test obtained p-value = 0.001 (p <0.05), indicating that there is a relationship between self-disclosure and stress levels in final year students. It is expected that students can improve their knowledge and good communication skills with self-disclosure to reduce stress levels. The results of the chi square statistical test obtained p-value = 0.001 (p <0.05), indicating that there is a relationship between self-disclosure and stress levels in final year students. It is expected that students can improve their knowledge and good communication skills with self-disclosure to reduce stress levels. The results of the chi square statistical test obtained p-value = 0.001 (p <0.05), indicating that there is a relationship between self-disclosure and stress levels in final year students. It is expected that students can improve their knowledge and good communication skills with self-disclosure to reduce stress levels.